Real-Time MRI Navigated Ultrasound for Preoperative Tumor Evaluation in Breast Cancer Patients: Technique and Clinical Implementation - Park, Ah Young (Korean J Radiol, 2016)
Real-time magnetic resonance imaging (MRI) navigated ultrasound is an image fusion technique to display the results of both MRI and ultrasonography on the same monitor. This system is a promising technique to improve lesion detection and analysis, to maximize advantages of each imaging modality, and to compensate the disadvantages of both MRI and ultrasound. In evaluating breast cancer stage preoperatively, MRI and ultrasound are the most representative imaging modalities. However, sometimes difficulties arise in interpreting and correlating the radiological features between these two different modalities. This pictorial essay demonstrates the technical principles of the real-time MRI navigated ultrasound, and clinical implementation of the system in preoperative evaluation of tumor extent, multiplicity, and nodal status in breast cancer patients.